Defective germanene as a high-efficiency helium separation membrane: a first-principles study. (1st March 2017) - Zhu, Lei; Chang, Xiao; He, Daliang; Xue, Qingzhong; Li, Xiaofang; Jin, Yakang; Zheng, Haixia; Ling, Cuicui
Abstract: Development of low energy cost membranes for separating helium from natural gas is highly desired. Using van der Waals-corrected first-principles density functional theory (DFT) calculations, we theoretically investigate the helium separation performance of divacancy-defective germanene. The 555 777 divacancy-defective germanene presents a 0.53 eV energy barrier for helium, which is slightly larger than the energy threshold value of gas molecule penetration of a membrane (0.5 eV). Thus, the 555 777 divacancy-defective germanene is difficult for helium to permeate, except under high temperature or pressure. However, the 585 divacancy-defective germanene presents a surmountable energy barrier (0.27 eV) for helium, and it shows extremely high helium selectivities relative to other studied gas molecules. Especially, the He/Ne selectivity can be as high as 1 × 10 4 at room temperature. Together with the acceptable permeance for helium, the 585 divacancy-defective germanene can be used for helium separation with remarkably good performance.